Construction of high density genetic linkage maps and fine mapping of quantitative trait loci associated with yield components and fatty acid composition in oil palm - Ting, Ngoot Chin (2018)
The African oil palm (Elaeis guineensis Jacq.) is a highly valued oil producing perennial crop with a productive lifespan of about 25 years. Although benefiting from a long productivity period, oil palm genetic improvement is a slow and tedious process which requires between 10 to 12 years to complete one selection cycle. As such, marker-assisted selection (MAS) is an invaluable tool for yield improvement in oil palm. In particular, MAS could be used to facilitate efforts to increase the unsaturated fatty acid content of palm oil by introgression of desired alleles from the American species, E. oleifera which produces highly unsaturated oil.